The Role of Sound in Film Translation: Subtitling Embodied Aural Experience in Aki Kaurismäki’s Lights in the Dusk - Kokkola, Sari (TTR, 2014)
The purpose of this article is twofold. First, by adopting a film studies-oriented approach to AVT it seeks to build common ground between translation studies and film studies—two disciplines that have remained curiously distant from each other, even though the film and translation industries are closely interrelated at the practical level. Second, by introducing study of the aural dimension of audiovisual texts—in particular film sound—to AVT, this article presents a new concept of text for AVT research that allows for the analysis of audiovisual texts as dynamic entities consisting of the visual, the aural and the verbal. These are seen as equally important constituent parts of audiovisual texts; they do not simply coexist but transform each other at the moment of perception. The role of sound in film translation is examined by applying phenomenologically informed theories of film sound, mainly Michel Chion’s (1994) theory of audio-vision, to the context of film subtitling. According to Chion, film viewing is based on cross-modal perception, i.e. synchronous sound and image are experienced as a unit, a “synchresis” (ibid., p. 63). Chion argues that filmic image and sound transform each other at the moment of perception, producing added value (ibid., p. 5). These audiovisual combinations not only address the viewer at the conceptual level but also contribute to the intensity and flow of the viewing experience that is to a large extent conveyed non-verbally. This paper argues that the translator’s decisions influence the added value created by image and sound and direct the viewer’s perception of a film, often overemphasizing the verbal element, thus narrowing the film’s non-verbally conveyed meanings and decreasing its emotional and esthetic appeal. These points are illustrated by presenting examples of the English and German subtitled versions of Aki Kaurismäki’s film Laitakaupungin valot (Lights in the Dusk).